The Prospects Of The Development Of Extreme Tourism In Uzbekistan - Zarif Oripovich Ahrorov; Bobur Baxtishodovich Sobirov (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
This article focuses on the development of extreme tourism in the context of developing various types of tourism. The purpose of the research is to reveal the significance of extreme tourism and to coverage of the work to be done in Uzbekistan in this regard. The work shows the structure of extreme tourism, SWOT analysis of its development in our country, as well as developed proposals for the development of extreme tourism.